A non-topological mechanism for negative linear compressibility. Issue 47 (20th May 2016) - Binns, Jack; Kamenev, Konstantin V.; Marriott, Katie E. R.; McIntyre, Garry J.; Moggach, Stephen A.; Murrie, Mark; Parsons, Simon
Abstract : When exposed to high pressure, the framework material UTSA-16 expands in one direction as the result of distortions localised in soft Co(ii )-based tetrahedra, rather than topological flexing of the network. Abstract : Negative linear compressibility (NLC), the increase in a unit cell length with pressure, is a rare phenomenon in which hydrostatic compression of a structure promotes expansion along one dimension. It is usually a consequence of crystal structure topology. We show that the source of NLC in the Co(ii ) citrate metal–organic framework UTSA-16 lies not in framework topology, but in the relative torsional flexibility of Co(ii )-centred tetrahedra compared to more rigid octahedra.